Meningkatkan Hasil Belajar Pakat dengan Model PBL Berbantuan LKPD Fase C Kelas VI SDN 101905 Pasar Melintang - Yellis Lingga; Dicky Aprianto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve learning outcomes in Catholic Religious Education (PAK) through the implementation of the Problem-Based Learning (PBL) model supported by Student Worksheets (LKPD) for Grade VI students in Phase C at SDN 101905 Pasar Melintang. The PBL model was chosen because it encourages students to think critically, creatively, and collaborate in solving problems relevant to daily life. LKPD was used as a supporting tool to help students understand the material and strengthen their active engagement in the learning process. This study employed a classroom action research method (PTK) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results showed a significant improvement in student learning outcomes after the application of the PBL model supported by LKPD. In the second cycle, the number of students achieving mastery scores increased compared to the first cycle. The implementation of PBL supported by LKPD proved effective in improving PAK learning outcomes for Grade VI students, while also enchancing their critical and collaborative thinking skills.